(untitled) - Ousby, Ian (New York, 1993)
The book gives full coverage both to the established classics of English literature and to the best-known writing of today, including works from all around the world: Britain and Ireland, the USA, Canada, the Caribbean, India, Africa, Australia and New Zealand. The book covers the writers - novelists, poets, playwrights, critics, journalists and essayists; the works - poems, novels, literary journals and plays. It also includes literary concepts and rhetorical terms, movements, groups and critical schools; children's literature, detective fiction and science fiction
Keywords: Commonwealth literature ( english ),English literature; Bio-bibliography,Dictionaries